ABOUT ONE METHOD OF PRESENTING THE TOPIC “COMPLEX NUMBER” - Beisebay, П.Б.; Mukhamediev, Ғ.Х. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2024)
In this article, teachers of a higher educational institution are offered a way to present the topic “Complex Number” to students and we share our opinion. In the course of presenting the topic, firstly, it is expected to give examples of problems that lead to the need to expand the search area for solutions not only to the set of vertex points of real numbers, but also to at least the set of points of the plane, i.e., the set of ordered pairs of real numbers. Subsequently, having shown that only the relations of addition, multiplication and equality characteristic of the set of real numbers can be introduced into the set , the set can be considered as a set of numbers other than real numbers, and since it is its element can be considered as complex of real numbers, set of complex numbers. It is justified that it is logical to name it. Then, having shown that it is possible to introduce into it a subset Z of the set of complex numbers with all relations characteristic of the set of real numbers, i.e., take it as the set of real numbers, it is proved that the set of complex numbers is indeed an extension of the set of real numbers, and any complex. It is shown that the number can be written as an algebraic expression , consisting of real numbers and one complex number. The authors present the topic with the idea that it will have a great impact on the complete assimilation of the topic materials.